You are on page 1of 19

Contents

• Forward z-transform
EN5101 Digital Control Systems
• Inverse z transform methods
z-Transforms – Power series, Recursive, Partial Fraction expansion

• z-transform Applications

• Applications of z-transform
– Pole-zero description of discrete-time systems
Prof. Rohan Munasinghe – Stability consideration
Dept of Electronic and Telecommunication Engineering – Difference Equations
University of Moratuwa
1 2

Discrete- time or sampled signal Analysis of Sampled Data Systems


x(n)

-2 -1 1 2 3 4 5 6 7 8 9 10 11 n

• A discrete time system is essentially a mathematical


algorithm that takes an input sequence, x(n), and produces
an output sequence, y(n).
• Example of discrete time systems are digital controllers,
digital spectrum analyzers, and digital filters.

x(n) Discrete time system y(n)


3 4
Problem with the Laplace in discrete systems
Laplace (Continuous) to z (Discrete)

5 6

The z-transform
Region of convergence (ROC) of Z- transform
• The z-transform of a sequence, x(n), which is valid for all
n, is defined as power series • The region of convergence (ROC) of X(z) is the set of all

values of z for which X(z) attains a finite value.
X ( z) =  x ( n) z
n = −∞
−n
• The region where the z-transform converges is known as
the region of convergence (ROC) and in this region, the
where X(z) = Z{x(n)} and z=rejω is a complex variable
values of X(z) are finite.
• In causal system x(n) = 0 for n < 0, x(n) may be nonzero • Thus, any time we cite a z-transform we should also
value only in the interval 0< n< ∞, so one sided z-transform indicate its ROC.
can be written as follow. ∞
X ( z ) =  x ( n) z − n
n =0

• Clearly, the z-transform is a power series with an infinite


number of terms and so may not converge for all values of z.
7 8
Solution:
Poles & Zeros of X(z) • To find poles and zeroes of X(z), denominator and numerator of
the X(z) are required to factorize first. Then,
• Values of z for which X(z) attains ∞ are referred to as
poles of X(z). 3 z 2 − 13z − 10 (3z + 2)( z − 5)
X ( z) = =
• Values of z for which X(z) attains 0 are referred to as the z 2 + 2z − 8 ( z + 4)( z − 2)
zeroes of X(z).
• To find poles, set the denominator of X(z) = 0
( z + 4) (z - 2) = 0
For example (z + 4) = 0 or (z - 2) = 0
3z 2 − 13z − 10 Thus, z = - 4 and z = 2 are poles of X(z).
X ( z) =
z 2 + 2z − 8
Find the poles and zeroes of X(z). • To find zeroes X(z) = 0 set the numerator of X(z)=0
i.e (3z + 2) (z - 5) = 0,
(3z + 2) = 0 or (z - 5) = 0
Thus, z = -2/3 and z = 5 are zeros of the X(z).
9 10

Example Solution
x1(n) = [1,2,5,7,0,1]
Determine the z-transform of the following finite-duration x1(n) is finite length sequence. It is causal case and having
signals. n = 0 to 5. Therefore,
• (a) x1(n) = [1,2,5,7,0,1] x1(0)=1, x1(1)=2, x1(2)=5, x1(3)=7, x1(4)=0, x1(5)=1
• (b) x2(n) = [1,2,5,7,0,1]
5
↑ X 1 ( z ) =  x1 (n) z − n
• (c) x3(n) = [0,0,1,2,5,7,0,1] n =0

• (d) x4(n) = [2,4,5,7,0,1] = x1 (0) z −0 + x1 (1) z −1 + x1 (2) z − 2 + x1 (3) z −3 + x1 (4) z − 4 + x1 (5) z −5


↑ = 1 + 2 z −1 + 5 z − 2 + 7 z −3 + 0 z −4 + 1z −5
• (e) x5(n) = δ(n) = 1 + 2 z −1 + 5 z − 2 + 7 z −3 + z −5
• (f) x6(n) = δ(n - k), k >0
The ROC is entire z-plane except at z = 0.
• (g) x7(n) = δ(n + k), k >0

11 12
X2(n) = [1,2, 5,7,0,1] (e) x5(n) = δ(n)
X2(n) is finite length sequence and double sided (non- By definition,
causal case) having n=-2 to 3. Therefore, 1 for n = 0
δ ( n) = 
x2(-2)=1, x2(-1)=2, x2(0)=5, x2(1)=7, x2(2)=0, x2(3)=1 0 else
3 By using general formula,
X2 (z) = x2 (n)z−n

n=−2

= x2 (−2)z−(−2) + x2 (−1)z−(−1) + x2 (0)z−0 + x2 (1)z−1 + x2 (2)z−2 + x2 (3)z−3


X ( z) =  x ( n) z
n = −∞
−n

−1 −2 −3
=1z + 2z + 5z + 7z + 0z +1z
2 1 0 ∞

= z + 2z + 5 + 7z + z
2 −1 −3
=  δ ( n) z
n = −∞
−n
= δ (0) z −0

= 1× 1 = 1
The ROC is entire z-plane except at z = 0 and z = ∞.
13 14

z Transform of a sampled unit step


Example
Determine the z-transform of the signal
x(n) = (1/2)n u(n).
Solution:

1 for n > 0
u (n ) = 
0 for n < 0
The signal x(n) consists of an infinite number of non-zero
samples for n> 0.
x(n) = [1, (1/2), (1/2)2, (1/2)3,…………, (1/2)n,….]
The z-transform of the x(n) is the infinite power series
X(z) = 1 + ½ z-1 + (1/2)2 z -2 + ……(1/2)n z -n +….

15 16
Example
∞ n ∞
1 1
X ( z ) =    z − n =  ( z −1 ) n Find the z-transform
and the region of
n=0  2  n =0 2
convergence for
• This is an infinite geometric series, we recall that each of the discrete-
time sequence
1
1 + a + a 2 + a 3 + ......... = if | a |< 1
1− a
where ‘a’ is the common ratio of the series. Consequently,

1
X (z) = if (1 / 2 ) z − 1 < 1
1 − (1 / 2 ) z − 1
ROC : | z |> 1 / 2

17 18
Fig 1 sample sequences

(b) Again, the sequence in figure 1(b) is not causal. It is of a


finite duration, and double sided.
(a) The z-transform is given by ∞ 5 3
∞ 6 0 X 2( z ) =  x ( n) z − n =  x ( n) z − n =  x ( n) z −n

X ( z) =  x (n) z
n = −∞
−n
=  x ( n) z
n = −7
−n
=  x ( n) z
n = −6
−n
n = −∞ n = −4 n = −3
− ( −3) − ( −2 )
X 1( z ) = (−6) z −( −6 ) + x(−5) z −( −5) + x(−4) z −( −4 ) + x(−3) z −( −3)
X 2( z ) = x(−3).z + x(−2).z + x(−1).z −( −1) + x(0).z −( 0 )
............... + x(−2) z −( −2) + x(−1) z −( −1) + x(0) z 0 ............. + x(1) z −1 + x(2).z − 2 + x(3) Z −3
X 1( z ) = 0 z −( −6 ) + 1z −( −5) + 3 z −( −4) + 5 z −( −3) + 3 z −( −2 ) + 1z −( −1) + 0 z 0 X 2 ( z ) = 0.z 3 + 1.z 2 + 3.z 1 + 5 z 0 + 3.z −1 + 1.z − 2 + 0.z −3
X 1 ( z ) = z 5 + 3z 4 + 5 z 3 + 3 z 2 + z1 X 2 ( z ) = z 2 + 3z + 5 + 3z −1 + z − 2
• It is readily verified that the value of X(z) becomes It is evident that the value of X(z) is infinite if z =0 or if
infinite when z = ∞. Thus the ROC is everywhere in z = ∞. So ROC is everywhere except z =0 and z = ∞.
the z- plane except at z = ∞.

19 20
(d) It is a causal sequence of infinite duration. The z-transform of the • Thus, power series of X4(z) converges if
sequence is given by:

z − 1 < 1 and equivalent ly if z > 1 .
X ( z) =  x ( n) z
n = −∞
−n

• Thus, we may express X (z) in closed form provided that region of


∞ ∞ convergence ( ROC) z > 1:
X 4( z ) =  z − n =  ( z −1 ) n
n =0 n =0

X 4 ( z ) = 1 + z + z − 2 + ......
−1 X ( z ) = 1 + z −1 + z −2 + ......
• This is a geometric series with a common ratio of Z-1. 1 z
X ( z) = =
• Generally, geometric series with a common ratio of ‘a’ can be
expressed as ∞ n
(1 − z −1 ) z − 1
1
n =0
a =
1 − a a < 1. • In this case, the z-transform is valid everywhere outside a circle of
• Which is a closed form of power series with common ratio ‘a’ and unit radius (ie |z| =1) whose centre is at the origin. The exterior of
the series converges if the circle is the region of convergence.

21 22

Z Transform of a sampled exponential

Unit Circle

The Unit Circle in the Complex The ROC of sequence (d), the
z- Plane shaded area is ROC

23 24
25 26

The inverse z transform


• where X(z) is the z-transform of x(n) and Z -1 is the
• The inverse z-transform (IZT) allows us to recover the symbol for the inverse z-transform.
discrete time sequence, x(n), given its z-transform X(z).
• Assuming a causal sequence, the z-transform, X(z)
• The inverse z-transform (IZT) is particularly useful in can be expanded into a power series as follow.
DSP work for example in finding the impulse response

of digital filters. X ( z ) =  x ( n) z − n
n =0

• Symbolically, the inverse z-transform may be defined X 3( z ) = x(0) + x(1) z −1 + x(2) z − 2 + x(3) z −3 + x(4) z − 4 + ......
as:
x(n) = Z -1 [X(z)] • It is seen that the values of x(n) are the coefficients of
z –n ( for n= 0, 1,2, ……) and so can be obtained
directly by inspection.

27 28
Power Series Method
• In practice, X (z) is often expressed as a ratio of two
polynomials in z -1 or equivalently in z, • Given the z-transform X(z) of a causal sequence, it can
be expanded into an infinite series in z -1 or z by long
division ( sometimes called synthetic division):
a0 + a1 z −1 + a2 z −2 + ...... + a N z − N
X ( z) = ........(4.1)
b0 + b1 z −1 + b2 z − 2 + ...... + bN z − M a0 + a1 z −1 + a2 z −2 + ...... + a N z − N
X ( z) =
b0 + b1 z −1 + b2 z − 2 + ...... + bN z − M
• In this form, the inverse z-transform, x (n), may be
obtained using one of several methods including the X ( z ) = x(0) + x(1) z −1 + x(2) z − 2 + x(3) z −3 + .......
following three:
(a) Power series expansion method • In this method, the numerator and denominator of X(z)
are first expressed in either descending powers of z or
(b) Recursive method
ascending powers of z -1 and the quotient is then
(c) Partial fraction expansion method obtained by long division.

29 30

Example
• Given the following z-transform of a causal LTI system,
obtain its IZT (Inverse Z- Transform) by expanding it into
a power series using long division:

1 + 2 z −1 + z −2
X ( z) =
1 − z −1 + 0.3561z − 2

First, we expand X(z) into a power series with the numerator


and denominator polynomials in ascending powers of z -1
and then perform the usual long division.
+ 3.6439

31 32
Recursive Method
a0 + a1 z −1 + a2 z −2 + ...... + a N z − N
X ( z) =
b0 + b1 z −1 + b2 z − 2 + ...... + bN z − M
x(0) = a0/b0
x(1) = [a1-x(0)b1]/b0
x(2)=[a2 – x(1)b1 – x(0)b2 ]/b0
Generally,
 n

x(n) = an −  x(n − i )bi  / b0 ,...n = 1,2,3...
 i =1 
where x(0) = a0/b0
We will repeat the previous example to illustrate the
recursive approach.
33 34

By using general equation, we have,


Example x(0) = a0/ b0 = 1/1 = 1
x(1) = [ a1 - x(0) b1]/ b0 = [2-1 × (-1)]/1 = 3
x(2) = [ a2 - x(1) b1- x(0)b2]/b0 = [1- 3 ×(-1) -1 ×0.3561]/1
Find the first four terms of the inverse z-transform, x (n), = 3.6439
using the recursive approach. Assume that the z-transform, x(3) = [ a3 - x(2) b1- x(1)b2 + x(0) b3]/ b0
X(z), is the same as in example 4.5, that is: = 0 – x(2) b1 – x(1)b2
1 + 2 z −1 + z −2 = [0 – 3.646439 × (-1) - 3 × 0.3561]/1 = 2.5756
X ( z) = X(4) = [ a4 - x(3) b1- x(2)b2 + x(1) b3 + x(0) b4 ]/ b0
1 − z −1 + 0.3561z − 2
= [0 -2.5756 × (-1) – 3.6439 × 0.356 + 3 × 0 + 1 × 0]/1
SOLUTION: = 2.5756 - 1.2972 + 0+0 = 1.2784
Comparing the coefficients of X(z) above with those of Thus the first four values of the inverse z-transform
the general transform, we have, are:
a0= 1, a1 = 2, a2 = 1, X(0) =1, x(1) = 3, x(2) = 3.6439, x(3) = 2.5756
b0= 1, b1 = -1, b2 = 0.3561,
It is seen that both the recursive and direct, long division
N=M=2 methods lead to identical solutions.
35 36
Partial fraction expansion method If the poles of X(z) are of first order, X(z) can be expanded
as:
a0 + a1 z −1 + a2 z −2 + ...... + a N z − N
• In this method, the z-transform is first into a sum of simple X ( z) =
partial fractions. The inverse z-transform of each partial
b0 + b1 z −1 + b2 z − 2 + ...... + bN z − M
C1 C2 CM
fraction is then obtained from z transform tables and then X ( z ) = B0 + −1
+ −1
+ ...... +
summed to give the overall inverse z-transform. 1 − p1 z 1 − p2 z 1 − pM z −1
C1 z C z C z
X ( z ) = B0 + + 2 + ...... + M
• In many practical cases, the z-transform is given as a ratio z − p1 z − p2 z − pM
of polynomials in z or z-1 and has the now familiar form. M
Ck z
........ = B0 +  ...................( 4.2)
k =1 z − pk
where pk are the poles of X(z) (assumed distinct), Ck are the
partial fraction coefficients and
B0 = aN/bN
37 38

• Case 1: If N ≤ M ie the order of the numerator is less • Case 3: If X(z) contains one or more multiple-order
than that of the denominator in X(z) expression, then B0 poles ( that is poles that are coincident) then extra
will be zero. terms are required in the partial fraction equation.
• Case 2: If N>M, then X(z) must be reduced first to make • For example, if X(z) contains an mth-order pole at
N ≤ M by long division.
z = pk the partial fraction expansion must include
• The coefficient, Ck, associated with the pole pk may be
terms of the form
obtained by multiplying both sides of the equation by (z -
pk) /z and then letting z = pk.

X ( z)
Ck = ( z − pk )
z z= pk

39 40
Example

The coefficients, Di, may be obtained from the relationship Find the inverse z-transform of the following transfer
function H(z).
(1 − z −1 )
H ( z) =
(1 − z −1 − 6 z − 2 )
Solution:
Since N < M, case 1.
Evaluation of inverse z-transforms by the partial fraction First, H(z) is converted for positive power of z.
expansion method is best illustrated by examples.

A B
H ( z) = +
(1 − 3 z ) (1 + 2 z −1 )
−1

41 42

To find A
2/5 3/ 5
A = H ( z )(1 − 3 z −1 ) | z −1 =1/ 3 H ( z) = +
(1 − 3 z ) (1 + 2 z −1 )
−1

1 − z −1 1 − z −1
A=
( −1 −1
1 − 3z (1 + 2 z )
1 − 3z −1
) ( ) =
(1 + 2 z −1 )
x ( n) = α n u ( n)
−1
z =1 / 3 −1
z =1 / 3 By comparing to the z transform
1
1−1/ 3 2/3 2 X ( z) =
A= = = 1 − αz −1
(1 + 2 ×1 / 3) 5 / 3 5
To find B The unit sample response of given system is:
B = H ( z )(1 + 2 z −1 ) | z −1 = −1/ 2 h(n) = (2/5)(3)nu(n) + 3/5 (-2)nu(n)
1 − z −1 1 − z −1 = [(2/5)(3)n + 3/5 (-2)n]u(n)
B=
( −1
) −1
1 − 3 z (1 + 2 z )
(
1 + 2 z −1 ) =
(1 − 3z −1 ) z −1 = −1/ 2
z −1 = −1/ 2

1 − ( −1 / 2) 1+1/ 2 3 / 2
B= = = = 3/ 5
1 − 3 × (−1 / 2) 1 + 3 / 2 5 / 2 43 44
Example • To change positive power of z by multiplying all terms
with z2 we get,
z
Find the inverse z-transform of the following X(z): X ( z) =
z − 0.25 z − 0.375
2

z −1
X ( z) = z
1 − 0.25 z −1 − 0.375 z − 2 X ( z) =
( z − 0.75)( z + 0.5)

Solution: X(z) contains first-order poles at z= 0.75 and at z= -0.5.


Since N< M, the partial fraction expansion has the form,
we get, N =1, M =2,
Thus, N<M Case 1: B0 =0 X ( z) 1 C1 C2
= = +
z ( z − 0.75)( z + 0.5) ( z − 0.75) ( z + 0.5)
45 46

To find C1 Then

( z − 0.75) X ( z) ( z − 0.75)1 X ( z) C1 C2 4/5 4/5


C1 = = = + = −
z z =0.75 ( z − 0.75)(z + 0.5) z =0.75 z ( z − 0.75) ( z + 0.5) ( z − 0.75) ( z + 0.5)
1 1 4 / 5.z 4 / 5.z
C1 = = = 4/5 X ( z) = −
( z + 0.5) z =0.75 (0.75 + 0.5) ( z − 0.75) ( z + 0.5)

From the z-transform table k an ⇔ k z /(z-a), therefore


To find C2
 4 / 5. z   − 4 / 5. z 
Z −1   = 4 / 5(0.75) n and Z −1   = −4 / 5(−0.5)
n

( z + 0.5) X ( z ) ( z + 0.5)1  ( z − 0. 75)   ( z + 0. 5) 


C2 = =
z z = −0.5 ( z − 0.75)( z + 0.5) z = −0.5
The desired inverse z-transform x(n) is then
1 1
C2 = = = −4 / 5
( z − 0.75) z = −0.5
(−0.5 − 0.75) x(n) = 4/5 [(0.75)n –(-0.5) n], n>0
47 48
The partial fraction expansion has the form,
X ( z) z C D1 D2
Example = = + +
z ( z − 0.5)( z − 1) 2
( z − 0.5) ( z − 1) ( z − 1) 2

Find the discrete-time sequence x(n) with the following z- ( z − 0.5) z z 0. 5


C= = = =2
transform 2 ( z − 0.5)( z − 1) 2 ( z − 1) 2 (0.5 − 1) 2
z = 0.5 z = 0.5
z
X ( z) =
( z − 0.5)( z − 1) 2 To obtain D1 ,
Solution: d  ( z − 1) 2 X ( z )  d  ( z − 1) 2 z  d  z 
D1 =   =  2
=  
dz  z  z =1 dz  ( z − 0.5)( z − 1)  z =1 dz  z − 0.5  z =1
X(z) has a first-order pole at z = 0.5 and a second order
pole at z =1.  (Case 3) d  z →u  vdu − udv
D1 =   =
dz  z − 0.5 → v  z =1 v2
( z − 0.5).1 − z.1 z − 0.5 − z − 0.5
D1 = = =
49 ( z − 0.5) 2
z =1 ( z − 0.5) z =1 ( z − 0.5) 2 z =1
2
50

Example
To obtain D2,

( z − 1) 2 X ( z ) z 1
D2 = = = =2
z z =1
z − 0.5 z =1 1 − 0.5
Combining the results, X(z) becomes,
2z 2z 2z
X ( z) = − +
( z − 0.5) ( z − 1) ( z − 1) 2
The inverse z-transform of each term on the right hand
side is obtained from table 1 and summed to give x(n) as
follows.

x(n) = 2(0.5)n – 2+ 2n=2[(n-1) + (0.5) n] , n ≥0

51 52
Properties of the z-transform Shifting Property
(1) Linearity Shifting a sequence (delaying or advancing) multiplies
the z-transform by a power of z, that is to say, if x(n)
If the sequences x1(n) and x2(n) have a z-transform X1(z) has a z-transform X(z)
and X2(z), then the z-transform of their linear combination
x(n – k) ⇔ z-kX(z)
is:
ax1(n) + bx2(n) ⇔ aX1(z) + bX2(z)
Shifting does not change the region of convergence.
Therefore, the z-transform of x(n) and x(n – k) have the same
and the ROC will include the intersection of Rx and Ry, that region of convergence.
is Rx ∩ Ry..
Eg. x(n-2) ⇔ z-2X(z)

53 54

z Transform of a shifted sequence


Properties: Time Reversal

If x(n) has a z-transform X(z) with a region of


convergence Rx that is the annulus α < |z| < β, the
z-transform of the time-reversal sequence x (-n) is

x (-n) ⇔ X(z -1)

and has a region of convergence 1/β < |z| < 1/α,


which is denoted by 1/Rx.

55 56
Properties: Convolution Theorem
Multiplication by an Exponential
Perhaps the most important z-transform property is the
convolution theorem, which states that convolution in the time
If a sequence x(n) is multiplied by a complex exponential αn, domain is mapped into multiplication in the frequency domain,
αnx(n) ⇔ X(α-1z) that is,

This corresponds to a scaling of the z-plane. If the region of


convergence of X(z) is r- < |z| < r+, which will be denoted by Rx, The region of convergence of Y(z) includes the interaction of Rx
the ROC of X(α-1z) is |α|r- < |z| < |α|r+, which is denoted by |α|Rx. and Ry, Rw contains Rx∩Ry However, the region of convergence
As a special case, note that if x(n) is multiplied by a complex of Y(z) may be larger, if there is a pole-zero cancellation in the
exponential, ejnω0, product X(z)H(z).
ejnω0x(n) ⇔ X(e-jω0z)
which corresponds to a rotation of the z-plane.

57 58

Real Convolution Theorem

Generalized
for any n

For a given n -
convolution
length

59 60
Example Properties: Derivative
Consider the two sequences
x(n) = αnu(n) and If X(z) is the z-transform of x(n), the z-transform of nx(n) is
h(n) = δ(n) - αδ(n – 1)
If y(n) is convolution of x(n) and h(n), find the sequence y(n)
Repeated application of this property allows for the evaluation of
Solution:
the z-transform of nkx(n) for any integer k.
The z-transform of x(n) is
X(z) = 1/(1 - αz-1) |z| > |α| and
the z-transform of h(n) is
H(z) = 1 - αz-1 |z| > 0

• However, the z-transform of the convolution of x(n) with


h(n) is Y(z) = X(z)H(z) = 1/(1 - αz -1)(1 - αz-1) = 1
• which, due to a pole-zero cancellation, has a region of
convergence, that is the entire z-plane. By taking Inverse
z-transform, y(n) = δ(n)
61 62

Table 2: Properties of z- transform Initial Value Theorem


Property Sequence z-Transform RoC
A property that may be used to find the initial value of a causal
Linearity ax(n) + by(n) aX(z) + bY(z) Contains Rx ∩ Ry sequence from its z-transform is the initial value theorem.

Shift x(n – n0) z − n0 X (z ) Rx If x(n) is causal, ie x(n)=0 for n<0], then

Time Reversal x(-n) X(z-1) 1/Rx


X(z) = x(0) + x(1)z-1 + x(2)z-2 + …
and
Exponential αnx(n) X(α-1z) αRx

x (0 ) = lim X ( z )
Convolution x(n) ∗ y(n) X(z) Y(z) Contains Rx ∩ Ry z→ ∞

Conjugation x*(n) X*(z*) Rx

dX ( z )
Derivative nx(n) −z Rx
dz

63 64
Example
Example
Let x(n) be a left-sided sequence that is equal to zero for n > 0.
If X(z) = (3z-1 + 2z-2)/(3 – z-1 + z-2), find x(0). Generalize the initial value theorem to find the value of
a causal sequence x(n) at n = 1, and find x(1) when
Solution: X(z) = (2 + 6z-1)/(4 – 2z-2 + 13z -3).
For a left-sided sequence that is zero for n>0, the
z-transform is X(z) = x(0) + x(-1)z + x(-2)z2 + ……….. Solution:
Therefore, it follows that If x(n) is causal,
x (0) = lim X ( z ) X(z) = x(0) + x(1)z-1 + x(2)z-2 + …
z →0
Therefore, note that if we subtract x(0) from X(z),
For the given z-transform, we see that X(z) – x(0) = x(1)z-1 + x(2)z-2 + …
3z −1 + 2z −2 z 2 3z + 2
x(0) = lim X (z) = lim −1 −2
× 2 = lim 2 =2 By multiplying both sides of this equation by z, we have,
z→0 z →0 3− z + z z z →0 3z − z + 1 z[X(z) – x(0)] = x(1) + x(2)z-1 + …

65 66

If we let z → ∞, we obtain the value for x(1), therefore, Then,


x(1) = zlim {z[X(z) – x(0)]} 6 z − 1 + z − 2 + 13 / 2 z − 3
→∞
z [ X ( z ) − x ( 0 )] = z ×
2 + 6 z −1 4 − 2 z − 2 + 13 z − 3
Example: For the z-transform X ( z ) =
4 − 2 z − 2 + 13z −3 6 + z −1 + 13 / 2 z − 2
z [ X ( z ) − x ( 0 )] =
2 + 6z −1 1 4 − 2 z − 2 + 13 z − 3
x(0) = lim X (z ) = lim − −
=
z →∞ z →∞ 4 − 2z 2
+13z 3
2
Then, X(z) – x(0) = X(z) - ½ is: Consequently,
1 2 + 6 z −1 1 x ( 1 ) = lim { z [ X (z ) − x ( 0 )]}
X ( z) − = −2 −3
− z→ ∞
2 4 − 2 z + 13 z 2
4 + 12 z −1 − 4 + 2 z − 2 − 13z −3 12 z −1 + 2 z − 2 − 13z −3 6 + z − 1 + 13 / 2 z − 2 3
= = x ( 1 ) = lim −2 −3
=
2(4 − 2 z − 2 + 13z −3 ) 2(4 − 2 z − 2 + 13z −3 )
z→ ∞ 4 − 2z + 13 z 2
6 z −1 + z − 2 − 13 / 2 z −3
=
(4 − 2 z − 2 + 13z −3 ) 67 68
The One-Sided z-Transform • Most of the properties of the one-sided z-transform are the
same as those for the two-sided z-transform. One that is
• The z-transform defined in previous section is the two- different, however, is the shift property.
sided, or bilateral, z-transform. The one-sided, or • Specifically, if x(n) has a one-sided z-transform X(z), the
one-sided z-transform of x(n – k) where k > 0 is:
unilateral, z-transform is defined by:
∞  k

X 1 (z ) = x ( n − k )  z − k  X 1 ( z ) +  x ( − n) z n 
 x(n )z −n
 n =1 
n =0
• Then, one-sided z-transform of x(n – 1) and x(n-2) are:
• The primary use of the one-sided z-transform is to solve
linear constant coefficient difference equations that have x(n − 1)  z −1 X 1 ( z ) + x(−1)
initial conditions.
x(n − 2)  z − 2 X 1 ( z ) + z −1 x(−1) + x(−2)

69 70

Example Therefore, taking the z-transform of both sides of the


difference equation,
Find the solution of the linear constant coefficient difference • y(n) = 0.25y(n – 2) + x(n), we have
equation • Y1(z) = 0.25[y(-2) + y(-1)z -1 + z-2Y1(z)] + X1(z)
y(n)=0.25 y(n–2) + x(n) for x(n)=δ(n–1) with y(-1)=y(-2)=1.
For x(n) = δ(n – 1)
Solution:
• X1(z) = z-1 × 1 = z-1
The given equation has initial conditions. Thus, We need to
apply one-sided z-transform to find its solution. If the one-
sided z-transform of y(n) is Y1(z), the one-sided z-transform Substituting for y(-1) and y(-2), and solving for Y1(z), we have
of y(n–2) is Y1(z) = 0.25[1 + z -1 + z-2Y1(z)] + z -1
∞ Y1(z) = ¼ + ¼ z -1 + ¼ z-2Y1(z)+ z -1
 y(n − 2) z
n=0
−n
= z −2Y1 ( z) + y(−1) z −1 + y(−2) Y1(z) - ¼ z-2Y1(z) = ¼ + 5/4 z -1
Y1(z)[1 - ¼ z-2] = ¼ [(1 + 5z-1)]
Y1(z) = ¼ (1 + 5z-1)]/ [1 - ¼ z-2]
71 72
(
A = H ( z ) 1 − 1 / 2 z −1 ) z −1 = 2
−1
1 / 4(1 + 5 z ) 1 / 4(1 + 5 z −1 )
• Y1(z) = ¼ (1 + 5z-1)]/ [1 - ¼ z-2] and it is equivalent to A=
(1 − 1 / 2 z −1 )(1 + 1 / 2 z −1 )
(
1 − 1 / 2 z −1 ) =
(1 + 1 / 2 z −1 ) z −1 = 2
z −1 = 2
1 / 4(1 + 5 z −1 ) 1 / 4(1 + 5 z −1 )
Y1 ( z ) = = 1 / 4(1 + 5 × 2) 11 / 4 11
(1 − 1 / 4 z − 2 ) (1 − 1 / 2 z −1 )(1 + 1 / 2 z −1 ) A= = =
1+1/ 2 × 2 2 8

• Y1(z) may be expanded by using partial fraction


expansions as follow. 1 / 4(1 + 5 z −1 ) 1 / 4[1 + 5(−2)]
B = H ( z )(1 + 1 / 2 z −1 ) = =
z −1 = −2 (1 − 1 / 2 z −1 ) z −1 = −2
1 − 1 / 2 × (−2)
1 / 4(1 + 5 z −1 )
Y1 ( z ) = −9/4
(1 − 1 / 2 z −1 )(1 + 1 / 2 z −1 ) B= = −9 / 8
2
A B
Y1 ( z ) = + 11 / 8 9/8
(1 − 1 / 2 z ) (1 + 1 / 2 z −1 )
−1
Then Y1 ( z ) = −
(1 − 1 / 2 z ) (1 + 1 / 2 z −1 )
−1

And y(n) = [(11/8)(1/2)n – (9/8)(-1/2)n]u(n)


73 74

Application of z Transforms in Discrete Car Loan Problem


Systems (Difference Equations)

HW: Solve for y(k)


75 HW: Solve for y(k) 76

You might also like